Non-Pharmacological Pain Management and its Effect on Pain of Children Postoperatively - Hend Nasser Thbeet, Adraa Hussein Shoq, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pediatric surgeries are common and painful for children. About 44 – 93% of pediatric patients have been reported to experience postoperative pain There is a growing trend toward the use of non-pharmacological techniques to supplement analgesia in children. The use of non - pharmacological methods can help reduce opioid intake and potentially harmful physiological and psychological responses to pain. Methods: A quasi-experimental study design was conducted on non-probability (purposive) convenience sample, consist of (90) child at age (3-12 years), selected from both gender at hospitals that provide surgical management for children in Al Amara city. The sample divided into (3) main groups include (30) child in each one, which also divided into (6) sub groups include (5) child in each one. Result: statistic shows that highest percentages of children experience (severe – very severe pain level) when assessed by OPS objective pain scale before applied any strategies to decrease their pain 13(43.4%) and 10(33.3%) respectively with arithmetic mean and standard division for group A (4.93 ∓ 1.552) which classified as severe pain. However, after applied the non-pharmacological pain strategies, most of children`s pain level was clearly decreased and high percentage of their pain was disappeared 13(43.4%) with arithmetic mean and standard division for group A (2.33 ∓ 2.682) which classified as mild pain. Conclusion: This study confirms the effectiveness of non-pharmacological pain management for children to decrease their pain after surgery and not depend on medication only.